2022
DOI: 10.1186/s13690-021-00761-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the long-term care insurance policy from medical expenses and health security equity perspective: evidence from China

Abstract: Background Since the national long-term care (LTCI) policy pilot in 2016 of China, the LTCI policy has had significant impact on the residents in the pilot area. Methods From the perspective of medical expenses and health security equity, this study selects tracking survey data from the CHARLS database in 2013, 2015, and 2018 and empirically investigates the effect of LTCI policy pilot by using differences-in-differences method (DID). Moreover, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 32 publications
2
18
0
Order By: Relevance
“…In this study, the three-period data from CHARLS in 2011, 2015, and 2018 were utilized to evaluate the health effects of LTCI on older residents within the triple difference framework. The empirical results demonstrated that the implementation of LTCI in China could effectively improve the SRH of older residents, which is consistent with the conclusion of a previous study 39 . Further analysis after separating the urban and rural samples illustrated that LTCI could only improve the SRH of urban older residents effectively and had no impact on older rural residents.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, the three-period data from CHARLS in 2011, 2015, and 2018 were utilized to evaluate the health effects of LTCI on older residents within the triple difference framework. The empirical results demonstrated that the implementation of LTCI in China could effectively improve the SRH of older residents, which is consistent with the conclusion of a previous study 39 . Further analysis after separating the urban and rural samples illustrated that LTCI could only improve the SRH of urban older residents effectively and had no impact on older rural residents.…”
Section: Discussionsupporting
confidence: 90%
“…However, the existing health production function does not consider the impact of the natural environment or air quality. Therefore, this study used individual ADL disability as a proxy for health variables and assumed that ADL disability is influenced by sociodemographic, regional environmental and individual health characteristics [ 45 ]. Here, sociodemographic characteristics include gender, age, household-registered marital status, etc.…”
Section: Methodsmentioning
confidence: 99%
“…As for China, many scholars also paid attention to this topic. Based on the China Health and Retirement Longitudinal Study (CHARLS) database in 2013, 2015 and 2018, Liu and Hu ( 23 ) assessed the impact of the long-term care policy pilot on residents' medical expenses and found that the policy significantly reduced the outpatient, inpatient and average daily hospitalization expenses of the elderly. Using the medical expenses data of internal and surgical inpatients of a hospital in Beijing from June 2016 to December 2019, Xiao et al ( 24 ) conducted a regression discontinuity design (RDD) to test the impact of the comprehensive reform of separation of medicine and pharmacy and the comprehensive reform of medical consumption linkage on residents' medical expenses, and the results showed that the two reforms significantly reduced the proportion of drugs and medical consumption.…”
Section: Literature Reviewmentioning
confidence: 99%